Operations management : an active learning approach - Bicheno, John.; Elliot, Brian (Malden, MA : Blackwell, 1997)
Introduction to operations management. Product planning and positioning. Process design. Managing demand and supply of materials. Project management. Quality management. Productivity, methods and measurements. Scheduling and capacity. Time based operations.
Keywords: Management; Production; Production management